Waste Management Practices of Beach Resorts in Biliran Province - Reymark Pabilando; Kenjie Caparro; Jeffrey Bantilan (Inclusive Society and Sustainability Studies, 2021)
A beach resort is a tourist spot, which is excellent for family outings and friends. It is a great place to relax and enjoy. Biliran has known for several different tourist spots, especially the beaches. Beach is one of the famous tourist spots, and those beaches are a haven for scuba divers because of the abundance of marine life. The study’s goal was to find out how beach resorts in Almeria, Biliran, dealt with waste. A descriptive research design was adopted in this study. It's descriptive in the sense that it describes beach resort trash management procedures. Leaves and seaweeds are the most general rubbish found at resorts, according to the findings of the study. According to the results, management should provide more training to employees to improve their knowledge of work and how to become more effective workers in their respective fields.